Heterogeneity of Beliefs and Trade in Experimental Asset Markets - Carlé, Tim A.; Lahav, Yaron; Neugebauer, Tibor; Noussair, Charles N. (Journal of Financial and Quantitative Analysis, 2019)
We investigate the relationship between traders’ expectations and market outcomes with experimental asset market data. The data show that those who have high price expectations buy more frequently and submit higher bids, and those who hold low price expectations sell more frequently and submit lower bids. Traders who have more accurate expectations achieve greater earnings. Simulations using only belief data reproduce the pricing patterns observed in the market well, indicating that the heterogeneity of expectations is a key to explaining market activity.